THE FILIPINO FAMILY – LIGHTS AND SHADOWS: Challenges to the Domestic Church - Lanaria, Levy Lara (Asian Horizons, 2013)
Vatican II’s retrieval of the notion of family as domestic church in its landmark document Lumen Gentium (n. 11) has provided impetus to the production of magisterial and theological reflections on the ecclesiological motif the last several decades. In the Philippines such titles attached to the Christian family as “the basic unit of Christian life,” “subject and object of evangelization,” “the primary community of Christ’s disciples,” “the church of the home,” or “the church in the home,” and “agent of renewal” have found their way in pastoral and theological discourse